USING KWL (KNOW, WANT, LEARNED) TECHNIQUE IN TEACHINGREADING COMPREHENSION - Susie Kusumayanthi; Ramles Volberson Silalahi (English Journal Literacy Utama, 2022)
The research is entitled “Using KWL (Know, Want, Learned) Technique in Teaching Reading Comprehension”. The aims of the research are to figure out how the teachers implement Know, Want, Learned (KWL) technique in teaching reading comprehension and the problems that raise when applying Know, Want, Learned (KWL) technique in teaching reading comprehension. This research uses descriptive qualitative method. The respondents of this study are two English teachers in one of the Vocational High Schools in Padalarang. The instruments used to collect data are interview and classroom observation. The results of data analysis showed that the teacher implemented all the steps of KWL (Know, Want, Learned) systematically during classroom activities based on what had been listed in the theory including (1) write a chart on the blackboard, (2) give topic about descriptive text and narrative text, (3) ask students to fill what they already know about the topic in column K, (4) asked students to fill what they want to know aboutthe topic in column W, (5) asked students to fill what they have learned about the topic in column L, and (6) make conclusions from the topic. The research finding also showed that the teachers faced some problems in implementing KWL (Know,Want, Learned) technique in teaching reading comprehension including students lack of background knowledge and students lack of vocabularies. This research is held based on the fact that although KWL has been found to help overcome problems encountered by teachers in getting the students to be more active to participate in the process of learning, but a vast amount of research about KWL in Indonesia, especially in vocational high school, has not been conducted, and there is still a great deal that is not known about the implementation of KWL in vocational high schools.